2003
DOI: 10.1002/ijc.10960
|View full text |Cite
|
Sign up to set email alerts
|

Human papillomavirus infection as a prognostic factor in carcinomas of the oral cavity and oropharynx

Abstract: Although studies have established human papillomaviruses (HPVs) as a risk factor for oral and oropharyngeal cancer, it is not clear whether viral infection affects survival in head and neck malignancies. This investigation examined the relationship between HPV and survival in carcinomas of the oral cavity and oropharynx. Formalin-fixed, paraffin-embedded tumor specimens from 139 newly diagnosed cases were tested for HPVs by PCR and DNA sequencing. Patient and tumor characteristics were obtained from questionna… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

26
356
11
15

Year Published

2006
2006
2012
2012

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 376 publications
(408 citation statements)
references
References 32 publications
26
356
11
15
Order By: Relevance
“…Other strong indicators for a favorable prognosis in our study include tumor diameter o4 cm, low/no expression of cyclin D1, and low/no tobacco consumption. In accordance with most other studies on HPV-related oropharyngeal carcinomas, we also found a favorable disease-specific survival in patients with HPV16-positive tonsillar squamous cell carcinomas, 12,46,[60][61][62][63][64] and p14 ARF overexpression, 31 although with less significance than the indicators described above. We noticed that lymph node status, which is generally considered as the most important prognostic factor in head-and-neck squamous cell carcinomas, 23 had little value in our series of tonsillar squamous cell carcinomas, which is in concordance with other studies.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Other strong indicators for a favorable prognosis in our study include tumor diameter o4 cm, low/no expression of cyclin D1, and low/no tobacco consumption. In accordance with most other studies on HPV-related oropharyngeal carcinomas, we also found a favorable disease-specific survival in patients with HPV16-positive tonsillar squamous cell carcinomas, 12,46,[60][61][62][63][64] and p14 ARF overexpression, 31 although with less significance than the indicators described above. We noticed that lymph node status, which is generally considered as the most important prognostic factor in head-and-neck squamous cell carcinomas, 23 had little value in our series of tonsillar squamous cell carcinomas, which is in concordance with other studies.…”
Section: Discussionsupporting
confidence: 92%
“…9 It has been shown that there are several differences between HPV-positive and -negative headand-neck squamous cell carcinomas. Despite the fact that HPV positivity in head-and-neck squamous cell carcinomas is an indicator for favorable prognosis, from a clinical point of view these tumors are often poorly differentiated 4,6,[10][11][12] and metastasized to lymph nodes at presentation. 10,11 Furthermore, HPV-positive tumors are often smaller at first diagnosis (diameter r4 cm), 13 and associated with low/no exposure to alcohol and tobacco.…”
mentioning
confidence: 99%
“…There is escalating evidence of a causal association between HPV and OSCC, [82][83][84][85][86][87][88][89][90][91][92][93] with several studies showing that HPV is associated with increased risk of oral cancer, independently of exposure to tobacco and alcohol. 84,86,88,89 This association is valid for high-risk HPV, which comprises subtypes 16, 18, 33, and 35.…”
Section: Review Of the Literature Patient-related Factorsmentioning
confidence: 99%
“…82,83,94 Recently published data on the prevalence of HPV infection in OSCC points to rates between 15% and 30%, but this might be an underestimation; it may ascend to more than 50%. 84,86,87,89,91 The disparity found in the published data has been associated with variations in collection of samples, the efficiency of the detection procedure, and geographic parameters. It is not well established how HPV infects the upper airway and oral cavity, but epidemiologic evidence suggests sexual transmission, 82,93 because the prevalence of infection increases after the onset of sexual activity, although the presence of HPV in OSCC has not yet been robustly linked to sexual practices such as oral sex.…”
Section: Review Of the Literature Patient-related Factorsmentioning
confidence: 99%
See 1 more Smart Citation